2013
DOI: 10.4238/2013.july.30.1
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 gene expression in pig populations and its association with resistance to Escherichia coli F18

Abstract: ABSTRACT. TLR4 is the main recognition receptor of bacterial lipopolysaccharides, which play an important role in innate and adaptive immunity. We used real-time PCR to analyze the tissue expression profile and differential expression of TLR4 in 4 pig populations (Escherichia coli F18-resistant Sutai, E. coli F18-sensitive Sutai, Large White, Meishan), in order to determine the role that the TLR4 gene plays in resistance to E. coli F18. We found that TLR4 expressed consistently in the 4 populations, with relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…TLR4 is an important member of TLR, which plays an important role in innate immunity and inflammation by sensing pathogen-associated molecular patterns [ 53 ]. It has been shown that TLR4 signaling in macrophages can activate hundreds of genes that contribute to the protection against bacterial infection [ 54 ]. Furthermore, 2‘-5’ oligoadenylates synthesis (OAS) is an antiviral protein induced by interferon, of which OASL belongs to this class of proteins [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 is an important member of TLR, which plays an important role in innate immunity and inflammation by sensing pathogen-associated molecular patterns [ 53 ]. It has been shown that TLR4 signaling in macrophages can activate hundreds of genes that contribute to the protection against bacterial infection [ 54 ]. Furthermore, 2‘-5’ oligoadenylates synthesis (OAS) is an antiviral protein induced by interferon, of which OASL belongs to this class of proteins [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the porcine intestinal epithelial IPEC-J2 cell line, the expression and the regulation of TLR4 after infection with an enteric virus has been reported (32). In 35-day-old weaned piglets, a very low level of expression in the jejunal tissue has been reported in comparison to the lung and the spleen (33). We determined the occurrence of CD14 on cells isolated from the intestinal epithelium of suckling and weaned piglets and found only CD45 + immune cells expressing mCD14.…”
Section: Discussionmentioning
confidence: 99%
“…85 Expression of TLR4 on macrophages and dendritic cells is increased upon exposure to E. coli, and subsequently, NF-κB activation and TNF-α secretion are both increased. 138 Higher expression of TLR4 does not always result in more effective resistance against E. coli, 139 but some expression seems to be essential for a reaction to E. coli. For example, a pair of twin infants that were both born with a TLR4 deficiency both quickly contracted a very rare brain abscess caused by E. coli.…”
Section: Tlr Rolementioning
confidence: 99%